Reading comprenhension and metacomprehension in university students using Intelligent Tutoring Systems (ITS) - Montenegro, Elizabeth (2025)
Reading comprehension and metacomprehension strategies pose a persistent challenge in higher education; consequently, Intelligent Tutoring Systems (ITS) have been developed to help students optimize both skills. This study assessed the impact of an ITS program, delivered with and without instructor support, against a control group using a pretest–postest experimental design to measure comprehension and metacomprehension. Participants who engaged with the ITS exhibited significant improvements in metacomprehension, whereas only those who received human tutoring showed superior gains in reading comprehension. These results suggest that, although ITS training alone enhances metacomprehension, the presence of a human tutor is critical for converting those gains into improved text comprehension.